(untitled) (Global Journal of Management and Business Research, 2019)
The paper is about understanding the current process in automation execution process and application of project management practices to it. The project is of automation of more than 6000 sites across the India for IOCL. The current model is waterfall model. After the study it is observed that there is lack of project management and project planning in the project. This affects the timeline and cost of project. The main objective is to introduce PM. Since agile practices are excellent for communication management and project controlling, the report proposes agile approach for current process. Since there are limitations for complete agile implementation, a mix approach, combining agile and waterfall can be used. Along with agile there are many other trends which can be applied to improve project efficiency. Report suggests visual project management, emotional intelligence as a tool for the project. Paper focuses on process and tools for implementation of risk management. It also checks the effectiveness of risk management plan.